CFD study on the correlation for a partially submerged orifice flow - Lee, Deric Kar Wai (2021)
The purpose of this study is to develop a CFD model that allows the correlation study for a partially submerged circular orifice flow in open channel. Three phenomena driven by gravity were included in this study, which are free discharge orifice (Case A), partially submerged orifice flow in downstream (Case B), and partially submerged orifice flow in both stream (Case C). Validation of model was carried out using Case A, yielding 0.35–38.05% deviation against the models from literature. The relationship between the volumetric flow rate with the orifice diameter and water level difference was analysed and the hypothesis that volumetric flow rate increases as the water level difference and orifice diameter increase in partial submerged condition was proven for Case B and C. Furthremore, the effect of orifice diameter to the volumetric flow rate was found out to be greater than that of the water level difference. Lastly, correlation of volumetric flow rate with water level difference and orifice diameter for Case B and C were determined through the model developed.